Synthesis of Linear Poly(ethylene glycol) Derivatives Based on Tripodal - Zhang, Yujun; Sheng, Xiaolei; Wang, Qinglu (Asian Journal of Chemistry, 2012)
A new and efficient method for the preparation of linear poly (ethylene glycol) derivatives based on tripodal is reported. In this method, six poly(ethylene glycol) derivatives have been synthesized in 85-92 % yields.